Incidence of Comorbidities in Women with Breast Cancer Treated with Tamoxifen or an Aromatase Inhibitor: An Australian Population-Based Cohort Study. Issue 1 (2018) - Ng, Huah Shin; Koczwara, Bogda; Roder, David; Niyonsenga, Theo; Vitry, Agnes
Background: The development of comorbidities has become increasingly relevant with longer-term cancer survival. Objective: To assess the pattern of comorbidities among Australian women with breast cancer treated with tamoxifen or an aromatase inhibitor. Design: Retrospective cohort study using Pharmaceutical Benefits Scheme (PBS) data (10% sample) from January 2003 to December 2014. Dispensing claims data were used to identify comorbidities and classified with the Rx-Risk-V model. The breast cancer cohort had tamoxifen or an aromatase inhibitor dispensed between 2004 and 2011 with no switching between types of endocrine therapy. Comparisons were made between the breast cancer cohort and specific control groups (age- and sex-matched at 1:10 ratio without any dispensing of anti-neoplastic agents during the study period) for the development of five individual comorbidities over time using Cox regression models. Results: Women treated with tamoxifen had a higher incidence of cardiovascular conditions, diabetes, and pain or pain-inflammation, but a lower incidence of hyperlipidaemia compared with non-cancer control groups, as indicated by PBS data. Women treated with aromatase inhibitors were more likely to develop cardiovascular conditions, osteoporosis, and pain or pain-inflammation compared with non-cancer control groups. The risks of hyperlipidaemia and osteoporosis were significantly lower among tamoxifen users compared with aromatase inhibitor users. Conclusions: Women with hormone-dependent breast cancer treated with an endocrine therapy had a higher risk of developing specified comorbid conditions than women without cancer, with different comorbidity profiles for those on tamoxifen versus aromatase inhibitors. Further research into the causes and mechanism of development and management of comorbidities after cancer is needed.